High-voltage smooth aluminum cable sheath hot melt adhesive and preparation method thereof

By using a special high -voltage and smooth aluminum cable protective hot melting glue in high -pressure cables, the problem of poor adhesion effects between cable protectives and aluminum sleeves is solved, and high -strength, water -resistant, and aging -resistant bonding effects are achieved.

CN119351002APending Publication Date: 2025-01-24HUANGSHAN BANNER TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411918481.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

In the prior art, the bonding effect between the smooth aluminum sleeve and the sheath material of the high-voltage cable is poor, resulting in the cable being easily eroded in humid environments, and the conventional asphalt coating process has the problem of poor interface bonding effect. .

Method used

A high -pressure and smooth aluminum cable protective hot melt glue, its ingredients include polar polyolefin elastomers, polar polyolefins, polyolefins, polyethyls, clusters, internal polytes, elastic bodies, and antioxidants. Mixing and dual screw extruded granulum processing.

Benefits of technology

It achieves a stable and reliable bonding effect for high-voltage smooth aluminum cable sheaths. The bonding strength is ≥10N/mm. The interface does not crack under 98°C hydrothermal conditions for 168 hours, and the bonding force does not decay at 100°C aging resistance for 168 hours.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of hot melt adhesives, and discloses a high-pressure smooth aluminum cable sheath hot melt adhesive and a preparation method thereof, and the high-pressure smooth aluminum cable sheath hot melt adhesive is prepared from the following components in parts by weight: 5-15 parts of a polar polyolefin elastomer, 5-15 parts of polar polyolefin, 5-30 parts of polyolefin, 20-40 parts of a polyolefin copolymer, 5-10 parts of a cohesion accelerator, 5-10 parts of an elastomer and 0.1-0.5 part of an antioxidant. The preparation method comprises the following steps: mixing the components in different parts by weight through a high-speed mixer, adding into a twin-screw extruder, and carrying out extrusion granulation at the extrusion temperature of 160-200 DEG C, the rotating speed of a main machine of 350-450rpm, the feeding rotating speed of 20-40rpm and the vacuum degree of less than or equal to 0.06 kpa. The prepared hot melt adhesive is specially used for bonding the high-pressure smooth aluminum sheath. According to the principle, metal interface bonding is achieved through polar polyolefin, bonding of the hot melt adhesive and a sheath material is achieved through similar compatibility, and the cohesive force and the failure mode of the hot melt adhesive are debugged through the cohesive force accelerant.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hot melt adhesives, and in particular to a high-voltage smooth aluminum cable sheath hot melt adhesive and a preparation method thereof. Background Art

[0002] The discharge and ablation between the semi-conductive buffer water-blocking layer and the corrugated aluminum sheath of the high-voltage cable is the primary cause of high-voltage cable failure. In order to solve this problem, a smooth aluminum sheath high-voltage cable was developed. The high-voltage smooth aluminum cable has a compact structure, and the smooth aluminum sheath and the buffer water-blocking layer are in close contact and have a small gap, which makes the cable water-blocking effect better; the smooth aluminum sheath and the outer shielding surface of the cable are in integral contact, with a large contact area, which reduces the induced current density on the surface of the aluminum sheath, effectively preventing the discharge phenomenon caused by poor contact of the internal buffer layer of the cable, and avoiding the discharge and ablation phenomenon inside the corrugated aluminum sheath high-voltage cable, which can better ensure the long-term operation safety of the cable. High-voltage cables are installed and laid underground or in a humid environment in tunnels for a long time. In order to protect the aluminum sheath of the cable from long-term erosion by moisture, acid and alkali, the standard stipulates that an anti-corrosion layer is applied to the outside of the aluminum sheath. However, in the production of smooth aluminum sheath high-voltage cables, it is found that the conventional asphalt coating process has many defects. The main reason is that the interface bonding effect is poor, and the asphalt cannot achieve reliable bonding between the aluminum tube and the sheath material. Therefore, it is urgent to develop new hot melt adhesives and their appropriate coating processes.

[0003] The industry mainly uses EAA (ethylene-acrylic acid copolymer) produced abroad as the adhesive layer material, but EAA is expensive and the supply is unstable, so there is an urgent need to develop hot melt adhesive that can replace EAA.

[0004] As a hot melt adhesive for bonding metal and sheath material (flame-retardant polyethylene substrate), to achieve a stable and reliable bonding effect, it is necessary to meet the following requirements: sufficient interface bonding strength and cohesive failure mode. The bonding effect is not good when ordinary polar polyolefins are used. The main reason is that the polar functional group content of polar polyolefins is much lower than the acrylic acid content in EAA, resulting in too few groups for interface reaction. In addition, the cohesive force of polyolefins is large, and the result of the peeling test is usually interface failure, the peeling force is very low, and sufficient interface bonding strength cannot be achieved. According to tests conducted by relevant domestic manufacturers, the test results of EAA bonding samples are also interface failures, which are difficult to achieve cohesive failure due to the large viscoelasticity and cohesive force of EAA. Even if there are a large number of interface reaction functional groups, it is still difficult to achieve cohesive failure. In addition, the peeling force of EAA bonding samples is significantly attenuated after the soaking test, and there is a potential risk of failure. On the contrary, the results of the soaking test of polar polyolefin bonding samples are better. How to achieve a balance between interface bonding strength and cohesive force by adjusting polar polyolefins and achieve high peeling force after cohesive failure is one of the technical difficulties.

[0005] In addition, the sheath material includes not only polyethylene substrate, but also polyvinyl chloride substrate sheath material. Polyethylene and polyvinyl chloride have very different polarities and are difficult to be compatible. Hot melt adhesives that bond polyethylene sheaths based on the principle of similar compatibility generally have difficulty in achieving good bonding effects on polyvinyl chloride sheaths. EAA hot melt adhesives and polyvinyl chloride sheath materials are completely non-adhesive. Therefore, developing a hot melt adhesive that can meet the bonding requirements of both substrates is the second technical difficulty. Summary of the invention

[0006] In order to solve the problems mentioned in the above background technology, the present invention provides a high-voltage smooth aluminum cable sheath hot melt adhesive and a preparation method thereof.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions: A high-voltage smooth aluminum cable sheath hot melt adhesive is prepared by including the following components in parts by weight: Polar polyolefin elastomer: 5-15 parts Polar polyolefin: 5-15 parts Polyolefin: 5-30 parts Polyolefin copolymer: 20-40 parts Cohesion promoter: 5-10 parts Elastomer: 5-10 parts Antioxidant: 0.1-0.5 parts.

[0008] Preferably, the polar polyolefin elastomer is one or a combination of maleic anhydride grafted ethylene octene copolymer, maleic anhydride grafted ethylene ethyl acetate, methyl methacrylate grafted ethylene octene copolymer, acrylic acid grafted ethylene octene copolymer, and maleic anhydride grafted ethylene methyl acrylate copolymer.

[0009] Preferably, the grafting rate of the polar polyolefin elastomer is 0.5-1.5%, and the melt index is 0.5-5g / 10min.

[0010] Preferably, the polar polyolefin is one or a combination of maleic anhydride grafted linear low density polyethylene, maleic anhydride grafted high density polyethylene, acrylic acid grafted medium density polyethylene, maleic anhydride grafted low density polyethylene, and maleic anhydride grafted ethylene methyl acrylate copolymer.

[0011] Preferably, the grafting rate of the polar polyolefin is 0.5-1.5%, and the melt index is 1.0-5g / 10min.

[0012] Preferably, the polyolefin is one or a combination of polyethylene, polypropylene, ethylene propylene copolymer, ethylene methyl acrylate copolymer, and ethylene ethyl acetate copolymer.

[0013] Preferably, the polyolefin copolymer is one or a combination of ethylene propylene copolymer, ethylene acrylic acid copolymer, ethylene methyl acrylate copolymer, ethylene ethyl acrylate copolymer, and ethylene ethyl acetate copolymer.

[0014] Preferably, the cohesion promoter is one or a combination of modified polystyrene, ABS, AS, PMMA, and PP, among which modified polystyrene is most preferred.

[0015] Preferably, the elastomer is one or a combination of ethylene propylene copolymer, ethylene butene copolymer, ethylene hexene copolymer, ethylene octene copolymer, and ethylene ethyl acetate copolymer.

[0016] Preferably, the antioxidant is one or more of antioxidant 1010, antioxidant 168, antioxidant 1076 or antioxidant B215.

[0017] Preferably, the method for preparing the modified polystyrene comprises the following steps: S1. Mix the silane coupling agent with deionized water to prepare a silane coupling agent solution with a mass concentration of 20-30%; S2, adding metal organic framework material (MOFs) and sodium carboxymethyl cellulose in a mass ratio of (3.2-5): (1.1-2) to the silane coupling agent solution prepared in S1, stirring at 45-60°C for 2-3h to obtain a mixed solution; S3. Add polystyrene matrix, benzoyl peroxide, N,N-dimethylbenzylamine and cationic modified graphene into the mixed solution, solidify at 110-120° C., and crush to obtain modified polystyrene.

[0018] MOFs and sodium carboxymethyl cellulose are added to the silane coupling agent solution in a certain mass ratio. The sodium carboxymethyl cellulose can act as a dispersant to prevent MOFs from agglomerating. On the one hand, MOFs react with the silane coupling agent and attach silane coupling agent molecules to their surface, which changes the surface properties of MOFs and makes them easier to interact with subsequent organic components.

[0019] On the other hand, functional groups such as carboxyl in the sodium carboxymethyl cellulose molecules undergo a certain degree of physical adsorption or chemical interaction with active groups on the surface of MOFs or silane coupling agent molecules, further stabilizing the system.

[0020] The pretreated MOFs form good interfacial interactions with the graphene and polystyrene matrix, and the final modified polystyrene has better mechanical properties and thermal stability.

[0021] Preferably, the preparation method of cation-modified graphene comprises the following steps: adding isopropanol and amination-modified graphene into a reactor, dispersing by ultrasonic oscillation, adding octadecyldimethylepoxyammonium chloride, heating to 70-85° C., reacting for 20-36 hours, filtering, washing with water and drying to obtain cation-modified graphene.

[0022] The added amount of octadecyl dimethyl epoxy ammonium chloride is 30-50% of the amination graphene.

[0023] The amination graphene is polyethylene glycol-amino modified, with an amino content of 10.1wt%, and is a planar modification.

[0024] In the preparation process of modified polystyrene, the present invention adds cation-modified graphene to make it uniformly dispersed in the polystyrene resin, thereby facilitating the improvement of the thermal decomposition temperature and heat resistance of the hot melt adhesive.

[0025] A method for preparing a high-voltage smooth aluminum cable sheath hot melt adhesive comprises the following steps: mixing the above-mentioned components in different weight portions by a high-speed mixer, adding the components into a twin-screw extruder for extrusion granulation, the extrusion temperature being 160°C-200°C, the main engine speed being 350-450rpm, the feed speed being 20-40rpm, and the vacuum degree being ≤0.06kpa.

[0026] The hot melt adhesive prepared by the invention is specially used for bonding high-pressure smooth aluminum sheaths.

[0027] The principle of the present invention is to achieve metal interface bonding through polar polyolefin, to achieve bonding between hot melt adhesive and sheath material through similar compatibility, and to adjust the cohesion and failure mode of hot melt adhesive through cohesion promoter.

[0028] Compared with the prior art, the present invention has the following beneficial effects: The hot melt adhesive of the present invention has the appearance of milky white or natural color particles, is easy to extrude and coat, has a bonding strength of ≥10N / mm, has no interface cracking under 98°C hydrothermal conditions for 168 hours, and has no bonding strength attenuation under aging resistance at 100°C for 168 hours.

[0029] By controlling the content of polar polyolefin, the chemical bonding between polyolefin and metal surface is regulated to achieve the purpose of interface bonding. The cohesion promoter is introduced to form an incompatible second phase, and the content is regulated to control the particle size and distribution of the second phase, reducing the cohesion of the matrix material; at the same time, polyolefin elastomer is added to regulate the winding density of the matrix resin molecular chain and improve the toughness of the material (resistance to cohesive failure or crack propagation); based on the appropriate ratio, cohesive failure is achieved while having high cohesive strength.

[0030] The cohesive failure with high peel force replaces the interfacial failure of copolymer hot melt adhesives (high polar content).

[0031] By controlling the type and proportion of the base resin, the purpose of making the hot melt adhesive and polyethylene or polyvinyl chloride miscible can be achieved, and the purpose of simultaneously bonding two materials with one hot melt adhesive can be realized, thus having high social use value and application prospects. DETAILED DESCRIPTION

[0032] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Unless otherwise specified, the raw materials used in the present invention are all conventional products purchased from the market.

[0034] Preparation Example 1 The preparation method of the modified polystyrene comprises the following steps: S1. Mix 50 g of silane coupling agent with 150 mL of deionized water to prepare a silane coupling agent solution with a mass concentration of 25%; S2, adding 32 g of MOFs and 20 g of sodium carboxymethyl cellulose to the silane coupling agent solution prepared in S1, and stirring at 60° C. for 2 h to obtain a mixed solution; S3. Add 50 g of polystyrene matrix, 5 g of benzoyl peroxide, 5 g of N,N-dimethylbenzylamine, and 10 g of cationic modified graphene into the mixed solution, solidify at 110° C., and crush to obtain modified polystyrene.

[0035] The preparation method of cation-modified graphene includes the following steps: adding 20g isopropanol and 30g amination graphene into a reactor, dispersing by ultrasonic oscillation, adding 12g octadecyldimethylepoxyammonium chloride, heating to 80°C, reacting for 30h, filtering, washing with water and drying to obtain cation-modified graphene.

[0036] Preparation Example 2 The preparation method of the modified polystyrene comprises the following steps: S1. Mix 50 g of silane coupling agent with 150 mL of deionized water to prepare a silane coupling agent solution with a mass concentration of 25%; S2, adding 45g MOFs and 15g sodium carboxymethyl cellulose to the silane coupling agent solution prepared in S1, and stirring at 60°C for 2h to obtain a mixed solution; S3. Add 50 g of polystyrene matrix, 5 g of benzoyl peroxide, 5 g of N,N-dimethylbenzylamine, and 10 g of cationic modified graphene into the mixed solution, solidify at 110° C., and crush to obtain modified polystyrene.

[0037] The preparation method of cation-modified graphene includes the following steps: adding 20g isopropanol and 30g amination graphene into a reactor, dispersing by ultrasonic oscillation, adding 12g octadecyldimethylepoxyammonium chloride, heating to 80°C, reacting for 30h, filtering, washing with water and drying to obtain cation-modified graphene.

[0038] Preparation Example 3 The preparation method of the modified polystyrene comprises the following steps: S1. Mix 50 g of silane coupling agent with 150 mL of deionized water to prepare a silane coupling agent solution with a mass concentration of 25%; S2, adding 50g MOFs and 20g sodium carboxymethyl cellulose to the silane coupling agent solution prepared in S1, and stirring at 60°C for 2h to obtain a mixed solution; S3. Add 50 g of polystyrene matrix, 5 g of benzoyl peroxide, 5 g of N,N-dimethylbenzylamine, and 10 g of cationic modified graphene into the mixed solution, solidify at 110° C., and crush to obtain modified polystyrene.

[0039] The preparation method of cation-modified graphene includes the following steps: adding 20g isopropanol and 30g amination graphene into a reactor, dispersing by ultrasonic oscillation, adding 12g octadecyldimethylepoxyammonium chloride, heating to 85°C, reacting for 36h, filtering, washing with water and drying to obtain cation-modified graphene. Example 1

[0040] A method for preparing a high-voltage smooth aluminum cable sheath hot melt adhesive, the hot melt adhesive being prepared from the following components in parts by weight: The polar polyolefin elastomer is maleic anhydride grafted ethylene ethyl acetate: 10 parts, the grafting rate is: 1.0%, and the melt index is 1.0g / 10min; The polar polyolefin is acrylic acid grafted medium density polyethylene: 15 parts, the grafting rate is: 1.5%, and the melt index is 0.8g / 10min; Polyolefin is polyethylene: 30 parts, melt index is 8g / 10min; The polyolefin copolymer is ethylene propylene copolymer: 30 parts, with a melt index of 8 g / 10 min; The cohesion promoter is the modified polystyrene in Preparation Example 1: 10 parts, with a melt index of 5 g / 10 min; The elastomer is ethylene butene copolymer: 5 parts, melt index is 5g / 10min, melting point is 96℃; Antioxidant 1010: 0.2 parts.

[0041] The above components of different weight portions are mixed in a high-speed mixer, added into a twin-screw extruder and granulated by extrusion. The extrusion temperature is 160°C, the main engine speed is 350rpm, the feed speed is 35 rpm, and the vacuum degree is ≤0.06kpa. Example 2

[0042] A method for preparing a high-voltage smooth aluminum cable sheath hot melt adhesive, the hot melt adhesive being prepared from the following components in parts by weight: The polar polyolefin elastomer is maleic anhydride grafted ethylene octene copolymer: 15 parts, grafting rate: 0.8%, melt index: 1.0g / 10min; The polar polyolefin is maleic anhydride grafted linear low-density polyethylene: 7 parts, grafting rate: 1.0%, melt index: 3.5g / 10min; Polyolefin is polyethylene: 20 parts, melt index is 18g / 10min; The polyolefin copolymer is ethylene ethyl acrylate copolymer: 40 parts, melt index is 10g / 10min, the elastomer melt index is 2g / 10min, and the melting point is 85°C; The cohesion promoter is the modified polystyrene in Preparation Example 2: 8 parts, with a melt index of 3.0 g / 10 min; The elastomer is ethylene octene copolymer: 10 parts, melt index is 5g / 10min, melting point is 96°C; Antioxidant B215: 0.1~0.5 parts.

[0043] The components with different weight portions are mixed in a high-speed mixer, added into a twin-screw extruder and granulated by extrusion. The extrusion temperature is 180°C, the main engine speed is 450rpm, the feed speed is 40rpm, and the vacuum degree is ≤0.06kpa. Example 3

[0044] A method for preparing a hot melt adhesive for a high-voltage smooth aluminum cable sheath, wherein the adhesive resin is prepared from the following components in parts by weight: The polar polyolefin elastomer is maleic anhydride grafted ethylene octene copolymer: 10 parts, the grafting rate is: 1.0%, and the melt index is 1.0g / 10min; The polar polyolefin is maleic anhydride grafted high-density polyethylene: 10 parts, the grafting rate is 0.8%, and the melt index is 3.0g / 10min; The polyolefin is linear low-density polyethylene: 25 parts, with a melt index of 8.0 g / 10 min; The polyolefin copolymer is ethylene methyl acrylate copolymer: 35 parts, with a melt index of 5.0 g / 10 min; The cohesion promoter is the modified polystyrene in Preparation Example 3: 10 parts, with a melt index of 5.0 g / 10 min; The elastomer is ethylene ethyl acetate copolymer: 10 parts, melt index is 5.0g / 10min, melting point is 80℃; Antioxidant 1076: 0.1 parts.

[0045] Components of different weight proportions are mixed in a high-speed mixer, added into a twin-screw extruder and granulated by extrusion. The extrusion temperature is 200°C, the main engine speed is 400rpm, the feed speed is 40rpm, and the vacuum degree is ≤0.06kpa.

[0046] Comparative Example 1 The difference between this comparative example and Example 1 is that the cohesion promoter is the modified polystyrene in Preparation Example 1 replaced by ordinary commercially available polystyrene purchased from Shanghai Youcheng International Trade Co., Ltd. with a product number of 622P.

[0047] Comparative Example 2 The difference between this comparative example and Example 1 is that the cohesion promoter is the modified polystyrene in Preparation Example 1 replaced by common commercially available ABS purchased from Shanghai Youcheng International Trading Co., Ltd. with a product number of PA-746.

[0048] The sample EAA (ethylene acrylic acid copolymer) was purchased from Alibaba with the item number 5200.

[0049] The hot melt adhesives obtained in Examples 1-3 and Comparative Examples 1-2 were subjected to the following performance tests: The mechanical strength of hot melt adhesive was tested according to GB / T 1040-2006, and the test temperature was 23°C; Peel force test: Tested in accordance with GB / T 2791; Water resistance test: According to GB / T 11547-1989, the test is carried out in a digital water bath, and the water heating temperature is 98℃; Aging test: The test is carried out in a specified aging oven according to GB / T 11547-1989, and aged for 168 hours at 100°C.

[0050] Melt index: According to GB / T3682-2000 standard, the melt flow rate tester is used for testing, the test load is 2.16kg, and the temperature is 190℃; The test results of the hot melt adhesives obtained in Examples 1-3 are shown in Table 1; the comparative examples 1-2 and the sample controls are shown in Table 2: Table 1 ; Table 2

[0051] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A high voltage smooth aluminum cable sheath hot melt adhesive, characterized in that: The preparation comprises the following components in parts by weight: Polar polyolefin elastomer: 5-15 parts Polar polyolefin: 5-15 parts Polyolefin: 5-30 parts Polyolefin copolymer: 20-40 parts Cohesion promoter: 5-10 parts Elastomer: 5-10 parts Antioxidant: 0.1-0.5 parts; The cohesion promoter is one of ABS, AS, PMMA and PP or a combination of several of them.

2. The high-voltage smooth aluminum cable sheath hot melt adhesive according to claim 1, characterized in that: The polar polyolefin elastomer is one or a combination of maleic anhydride grafted ethylene octene copolymer, maleic anhydride grafted ethylene ethyl acetate, methyl methacrylate grafted ethylene octene copolymer, acrylic acid grafted ethylene octene copolymer, and maleic anhydride grafted ethylene methyl acrylate copolymer; The grafting rate of the polar polyolefin elastomer is 0.5-1.5%, and the melt index is 0.5-5g / 10min.

3. The high-voltage smooth aluminum cable sheath hot melt adhesive according to claim 1, characterized in that: The polar polyolefin is one or a combination of maleic anhydride grafted linear low-density polyethylene, maleic anhydride grafted high-density polyethylene, acrylic acid grafted medium-density polyethylene, maleic anhydride grafted low-density polyethylene, and maleic anhydride grafted ethylene methyl acrylate copolymer; The grafting rate of polar polyolefin is: 0.5~1.5%, and the melt index is 1.0-5g / 10min.

4. The high-voltage smooth aluminum cable sheath hot melt adhesive according to claim 1, characterized in that: The polyolefin is one or a combination of polyethylene, polypropylene, ethylene propylene copolymer, ethylene methyl acrylate copolymer, and ethylene ethyl acetate copolymer.

5. The high-voltage smooth aluminum cable sheath hot melt adhesive according to claim 1, characterized in that: The polyolefin copolymer is one or a combination of ethylene propylene copolymer, ethylene acrylic acid copolymer, ethylene methyl acrylate copolymer, and ethylene ethyl acetate copolymer.

6. The high-voltage smooth aluminum cable sheath hot melt adhesive according to claim 1, characterized in that: The elastomer is one or a combination of ethylene propylene copolymer, ethylene butene copolymer, ethylene hexene copolymer, ethylene octene copolymer, and ethylene ethyl acetate copolymer; The antioxidant is one or more of antioxidant 1010, antioxidant 168, antioxidant 1076 or antioxidant B215.

7. The high-voltage smooth aluminum cable sheath hot melt adhesive according to claim 1, characterized in that: The cohesion promoter also includes modified polystyrene.

8. The high-voltage smooth aluminum cable sheath hot melt adhesive according to claim 7, characterized in that: The preparation method of the modified polystyrene comprises the following steps: S1. Mix the silane coupling agent with deionized water to prepare a silane coupling agent solution with a mass concentration of 20-30%; S2, adding MOFs and sodium carboxymethyl cellulose in a mass ratio of (3.2-5): (1.1-2) to the silane coupling agent solution prepared in S1, stirring at 45-60°C for 2-3h to obtain a mixed solution; S3. Add polystyrene matrix, benzoyl peroxide, N,N-dimethylbenzylamine and cationic modified graphene into the mixed solution, solidify at 110-120° C., and crush to obtain modified polystyrene.

9. The high-voltage smooth aluminum cable sheath hot melt adhesive according to claim 8, characterized in that: The preparation method of the cation-modified graphene comprises the following steps: adding isopropanol and amination-modified graphene into a reactor, dispersing by ultrasonic oscillation, adding octadecyldimethylepoxyammonium chloride, heating to 70-85° C., reacting for 20-36 hours, filtering, washing with water and drying to obtain the cation-modified graphene; The added amount of octadecyl dimethyl epoxy ammonium chloride is 30-50% of the amination graphene.

10. A method for preparing a high-voltage smooth aluminum cable sheath hot melt adhesive, comprising preparing the high-voltage smooth aluminum cable sheath hot melt adhesive as claimed in any one of claims 1 to 9, characterized in that: The following steps are also included: The components in parts by weight are mixed in a high-speed mixer, added into a twin-screw extruder and granulated by extrusion. The extrusion temperature is 160° C.-200° C., the main engine speed is 350-450 rpm, the feed speed is 20-40 rpm, and the vacuum degree is ≤0.06 kpa.

Citation Information

Patent Citations

  • Low-shrinkage and heat-resistant adhesive resin and preparation method thereof

    CN113150720A

  • Low activation temperature adhesive composition with high peel strength and cohesive failure

    CN1378579A

  • Polar group-containing olefin copolymer, thermoplastic resin composition containing the copolymer and use thereof

    JP2002145947A

  • Low activation temperature adhesive composition with high peel strength and cohesive failure

    WO2001018141A1